2023
DOI: 10.1002/ece3.9913
|View full text |Cite
|
Sign up to set email alerts
|

Callicarpa stoloniformis (Lamiaceae), a new species from Southeast China based on morphological characters and phylogenetic evidence

Abstract: Callicarpa stoloniformis sp. nov. (Lamiaceae) is described as a new species from Fujian Province of China on the basis of both morphological and molecular data. The new species is morphologically most close to C. hainanensis. However, it can be distinguished from the latter by its unique procumbent life form, adventitious roots at nodes, papery leaves, cup-shaped or campanulate calyx, truncate or shallow fissure calyx lobes, and smaller fruits. In addition, the new species is also similar with C. basitruncata,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Sixteen Chinese Callicarpa species ( Ma et al 2023 ) were selected as representatives for phylogenetic analysis, with Dasymalla teckiana (F. Muell.)…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen Chinese Callicarpa species ( Ma et al 2023 ) were selected as representatives for phylogenetic analysis, with Dasymalla teckiana (F. Muell.)…”
Section: Materials and Methodsmentioning
confidence: 99%
“…A total of 48 species in the genus Callicarpa were catalogued in the Flora of China ( Chen and Michael 1994 ). Later, four new species, including C. hainanensis Z. H. Ma & D. X. Zhang ( Ma and Zhang 2012 ), C. pararubella Qiang Wang ( Wang 2019 ), C. stoloniformis X. X. Su, Z. H. Ma & B. Chen ( Ma et al 2023 ) and C. liuliana Z. H. Chen, W. Y. Xie & F. Chen ( Xie et al 2023 ), were reported and a new combination C. subglabra (C. Pei) L. X. Ye & B. Y. Ding was proposed ( Ye et al 2018 ). Thus, to date, a total of 53 Callicarpa species have been reported to be distributed in China.…”
Section: Introductionmentioning
confidence: 99%